2022
DOI: 10.1002/slct.202103556
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Mechanical Performance of Glass Fiber Reinforced, Three‐phase, Epoxy Syntactic Foam

Abstract: In the selection of materials for deep‐sea equipment, light weight and high strength are the most important criteria or requirements. In this paper, hollow glass microspheres (HGMS), expanded polystyrene (EPS), epoxy resin (EP) and curing agent were mixed to prepare hollow glass microspheres reinforced epoxy foam balls (HGMS‐EHS) by the rolling ball method. Glass fiber (GF) reinforced epoxy syntactic foam (GF‐ESF) was prepared by mixing HGMS‐EHS, HGMS, EP, GF, and curing agent using compression moulding method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…When lightweight concrete is impacted by an external force, the force is rapidly transferred from the concrete matrix to the GFR-EMS and from the GFR-EMS to the cement matrix or another GFR-EMS. 43 The strength of the GFR-EMS is lower than that of the cementitious matrix. Damage begins with the GFR-EMS and then passes rapidly to the next GFR-EMS or the adjacent matrix above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When lightweight concrete is impacted by an external force, the force is rapidly transferred from the concrete matrix to the GFR-EMS and from the GFR-EMS to the cement matrix or another GFR-EMS. 43 The strength of the GFR-EMS is lower than that of the cementitious matrix. Damage begins with the GFR-EMS and then passes rapidly to the next GFR-EMS or the adjacent matrix above.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the GFR-EMS were connected to each other close to form lines. When lightweight concrete is impacted by an external force, the force is rapidly transferred from the concrete matrix to the GFR-EMS and from the GFR-EMS to the cement matrix or another GFR-EMS . The strength of the GFR-EMS is lower than that of the cementitious matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The composites exhibited electromagnetic interference shielding properties whilst the HGMSs acted as materials to fill up the vacancies generated by the network of carbon fibers. Jiang et al [18] have recently revealed their work on the use of HGMSs in reinforcing expanded polystyrene (EPS) and epoxy resin (EP) to develop compression molded foam balls of enhanced compressive strength. In another study, Altay et al [19] incorporated HGMSs together with polystyrene (PS) microfiber membrane to examine the effect of HGMSs on the thermal insulation and sound absorption insulation behavior of glass fiber fabric-reinforced epoxy composites.…”
Section: Introductionmentioning
confidence: 99%